1968
DOI: 10.1210/endo-82-1-193
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Female Sex Behavior in Adrenalectomized Rats with Estrogen Alone

Abstract: Apparently normal sex behavior was produced in spayed rats by daily injections of 0.8 or 3.2 /*g estradiol benzoate. Adrenalectomy had no deleterious effect on this behavior. Uterine weight data suggested that the lower dose produced circulating estrogen levels within or below those occurring in physiological conditions. Since, in the combined ovariectomized-adrenalectomized females, all known sources of steroid hormones were removed, it is concluded that the expression of sexual receptivity in female rats doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(36 citation statements)
references
References 2 publications
5
31
0
Order By: Relevance
“…1), in the gonadally intact state, some females allowed males to mount, exhibiting enough elements of sexual receptivity to permit vaginal deposition of sperm by the male (Movie S2). Such observations are consistent with previous reports showing estrogen alone can facilitate sexual behavior in the rat (21,22). The mating never yielded a pregnancy or pseudopregnancy; instead, Pgr Δ136E1 null female rats continued to cycle.…”
Section: Significancesupporting
confidence: 92%
“…1), in the gonadally intact state, some females allowed males to mount, exhibiting enough elements of sexual receptivity to permit vaginal deposition of sperm by the male (Movie S2). Such observations are consistent with previous reports showing estrogen alone can facilitate sexual behavior in the rat (21,22). The mating never yielded a pregnancy or pseudopregnancy; instead, Pgr Δ136E1 null female rats continued to cycle.…”
Section: Significancesupporting
confidence: 92%
“…As expected, E2, E2 + P4, and T, but not P4 alone, also increased reproductive behavior and uterine weight, although to varying extents. As shown previously in studies of reproductive behavior, E2 by itself almost fully restored lordosis behavior and uterine weight to that observed in sham-estrus females, and P4 by itself had no effect on lordosis (Davidson et al, 1968;Young, 1961). In contrast, T only partially restored lordosis, and slightly, but not significantly, increased uterine weight above that in GDX control females.…”
Section: Effects Of Gonadal Steroid Manipulations In Femalessupporting
confidence: 79%
“…Surgery (gonadectomy or sham-gonadectomy) was performed in rats that were approximately 3 months old. In all rats except sham females, basal nociception and morphine antinociception were tested 28 days after surgery, when endogenous hormone levels and associated reproductive behaviors have been shown to be minimal in GDX rats (Young, 1961;Davidson, 1966;Davidson et al, 1968;Damassa et al, 1977). Sham females were tested between 21 and 35 days post-surgery so that females in diestrus, proestrus and estrus could be identified and tested in approximately equal numbers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ovariectomized animals, however, estrogen alone elicits the lordosis reflex, a major receptive component of female rat sexual behavior, provided that estrogen is given in large doses for a prolonged period [2][3][4]. Although certain estrogen actions depend on cross-talk between estrogen-and progestin-receptor signaling pathways [5], experiments that employed progestinreceptor blocker [6], antisense oligonucleotides to progestin receptor [7] or progestin-receptor knockout mice [8] showed that progestin receptors are not involved in the estrogen-induced Lordosis reflex.…”
mentioning
confidence: 99%